2020
DOI: 10.3906/sag-1901-69
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the effect of percutaneous mitral balloon valvuloplasty on left ventricular systolic functions using strain and strain rate echocardiography

Abstract: Background/aim: This study aimed to evaluate the effect of successful percutaneous mitral balloon valvuloplasty (PMBV) on left ventricular systolic functions using strain and strain rate echocardiography in moderate-severe mitral stenosis (MS) patients with normal left ventricular systolic function confirmed by conventional echocardiography. Materials and methods: Patients with moderate-severe MS who had undergone successful PMBV were included. Conventional echocardiographic parameters were evaluated before an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…After PBMV, a Doppler study indicated a considerable improvement in the overall function of the left ventricle [5].…”
Section: Discussionmentioning
confidence: 98%
“…After PBMV, a Doppler study indicated a considerable improvement in the overall function of the left ventricle [5].…”
Section: Discussionmentioning
confidence: 98%
“…Chen et al, in a multicenter study, which included 4832 (70% female) MS patients, the procedure success rate was 99%. 21 Güntürk EE et al 23 successfully performed PMBV (mean MCA increased from 1.1 cm 2 to 1.6 cm 2 ) in 30 patients, 80% of whom were women, with a mean age of 32 years, and did not report any significant cardiovascular complications. 23 In another study, Tomai F et al 24 , studied a total of 482 consecutive patients, and successful PMBV treatment was achieved in 91% of patients.…”
Section: Discussionmentioning
confidence: 99%
“…21 Güntürk EE et al 23 successfully performed PMBV (mean MCA increased from 1.1 cm 2 to 1.6 cm 2 ) in 30 patients, 80% of whom were women, with a mean age of 32 years, and did not report any significant cardiovascular complications. 23 In another study, Tomai F et al 24 , studied a total of 482 consecutive patients, and successful PMBV treatment was achieved in 91% of patients. The group of 45 (8.5%) patients had suboptimal valve dilation (post-PMV valve area <1.5 cm 2 ), severe MR, and need for surgery (repair or replacement).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have examined these parameters in MS ( 14) and analyzed how they changed following PBMV (15,16). The lack of investigation of the PBMV effects by strain and strain rate imaging was acknowledged as a limitation by the authors themselves.…”
Section: Figure 1 the Effects Of Pbmv On Ventricular Function In Pati...mentioning
confidence: 99%
“…The lack of investigation of the PBMV effects by strain and strain rate imaging was acknowledged as a limitation by the authors themselves. Multiple studies have already suggested to perform early PBMV in patients with confirmed subclinical LV dysfunction, even if they are still asymptomatic (7,15). Indeed, an inverse correlation was noted between baseline MPI and the magnitude of change in MPI after PBMV, implicating that intervening before significant worsening of LV function may produce better long-term outcomes (7).…”
Section: Figure 1 the Effects Of Pbmv On Ventricular Function In Pati...mentioning
confidence: 99%